MUS81 Inhibition Enhances the Anticancer Efficacy of Talazoparib by Impairing ATR/CHK1 Signaling Pathway in Gastric Cancer - Wang, Tao; Zhang, Peng; Li, Chengguo; Liu, Weizhen; Shen, Qian; Yang, Lei; Xie, Gengchen; Bai, Jie; Li, Ruidong; Tao, Kaixiong; Yin, Yuping (Frontiers in Oncology, 2022)
MUS81 is a critical endonuclease involved in heterodimer formation with Eme1⁄Mms4 and an important DNA damage repair regulatory molecule. Our previous study suggested that MUS81 was overexpressed and its high expression was positively correlated with gastric cancer metastasis. However, the therapeutic potential of targeting MUS81 in gastric cancer requires further exploration. Therefore, in this study, the Cancer Genome Atlas (TCGA) data were analyzed and showed that MUS81 is a key regulator of cell cycle distribution and DNA damage repair in gastric cancer. In vitro and in vivo, MUS81 knockdown significantly enhanced the anticancer effect of the PARP inhibitor talazoparib. Mechanistically, MUS81 inhibition impaired the activation of the ATR/CHK1 cell cycle signaling pathway and promoted gastric cancer cells with talazoparib-induced DNA damage to continue mitosis. Moreover, addition of the bromodomain-containing protein 4 inhibitor AZD5153 increased the anticancer effect of talazoparib via MUS81 inhibition in gastric cancer cells, and this combination effect was largely impaired when MUS81 was knocked down. In conclusion, these data suggested that MUS81 regulated ATR/CHK1 activation, a key signaling pathway in the G2M checkpoint, and targeting MUS81 enhanced the antitumor efficacy of talazoparib. Therefore, AZD5153 combined with talazoparib may represent a promising therapeutic strategy for patients with MUS81 proficient gastric cancer.